Political risk: Not just the investor's affair - Xavier M. Forneris (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2019)
Assessing, managing and minimizing political risk is a key component in investment decisions. Given that many factors of political risk are within the control of governments, this Perspective proposes specific actions countries should take to make minimizing political risks a central part of their investment promotion strategy.
Keywords: 330